(untitled) (Hoboken, N.J., 2006)
Divided into six comprehensive parts, Advanced Bond Portfolio Management will guide you through the state-of-the-art techniques used in the analysis of bonds and bond portfolio management.
Keywords: Portfolio management,Bonds; Trái phiếu,Quản lý doanh mục đầu tư